2017
DOI: 10.1073/pnas.1607948114
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Rift Valley fever epidemics in Madagascar

Abstract: Rift Valley fever (RVF) is a vector-borne viral disease widespread in Africa. The primary cycle involves mosquitoes and wild and domestic ruminant hosts. Humans are usually contaminated after contact with infected ruminants. As many environmental, agricultural, epidemiological, and anthropogenic factors are implicated in RVF spread, the multidisciplinary One Health approach was needed to identify the drivers of RVF epidemics in Madagascar. We examined the environmental patterns associated with these epidemics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…This might well have happened in 2010, when an RVF outbreak occurred in northern Mauritania after exceptional rainfall: Mauritanian farmers brought their animals (small ruminants, cattle, dromedaries)—and most likely the RVF virus as well, from southern Mauritania by truck to benefit from the unexpected resources in surface water and grasslands [ 52 , 53 ]. Antibodies against RVF virus were later found in Moroccan dromedaries [ 54 ], suggesting that the spread of this virus in Morocco had occurred via livestock trade, as it had been the case between the Horn of Africa and the Arabic peninsula in 2000 [ 55 ], or between the East African mainland and the Comoros Archipelago—and Madagascar in 2006-2008 [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might well have happened in 2010, when an RVF outbreak occurred in northern Mauritania after exceptional rainfall: Mauritanian farmers brought their animals (small ruminants, cattle, dromedaries)—and most likely the RVF virus as well, from southern Mauritania by truck to benefit from the unexpected resources in surface water and grasslands [ 52 , 53 ]. Antibodies against RVF virus were later found in Moroccan dromedaries [ 54 ], suggesting that the spread of this virus in Morocco had occurred via livestock trade, as it had been the case between the Horn of Africa and the Arabic peninsula in 2000 [ 55 ], or between the East African mainland and the Comoros Archipelago—and Madagascar in 2006-2008 [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to little existing data on RVF, those mechanisms have not been fully quantified. Previous work on RVF emergence conducted for the Horn of Africa using ecological statistical modelling showed that above-average rainfall and vegetation density (Normalized Vegetation Difference Index, NDVI) over 3 to 4 months could lead to RVF re-emergence [ 10 ], but it did not seem to be always the case, especially in Madagascar and Southern Africa, where other factors, such as the movements of animals or the level of livestock susceptibility may also play a role [ 11 , 12 ]. Finally, although a range of mathematical models have been developed to study RVF, they looked mainly at RVF spread, that is once the virus is introduced [ 13 ] or they assessed the impact of vaccination strategies [ 14 ], and only few were fitted to data [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…U. The real world is much more complex, with intense livestock movements (trade, transhumance) possibly associated with the introduction of non-immunized animals, or even pathogen agents [ 58 , 59 ]. Therefore, it is important to maintain the vaccination coverage (introduced animals should be immunized), and to prevent the introduction of the virus once the vaccination has ceased.…”
Section: Discussionmentioning
confidence: 99%